Napas Hijau Gunung Kawi : Etnobotani Tumbuhan dalam Ritual dan Pengobatan Tradisional Masyarakat Sekitar Desa Balesari - Baqtiar Rizki Romadhon; Fanda Vebriani; Pranadya Ananta Lesta Zaen; Salma Aulia Putri; Fahrul Ghani Muhaimin; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Syifa Nabila Firdausya; Heni Refdiana; Anas Bagaskara Witanto; Susriyati Mahanal (Biocaster : Jurnal Kajian Biologi, 2026)
This research is motivated by the lack of documentation of the use of ritual plants and traditional medicine by the Balesari village community, which is threatened with extinction due to modernization. In addition, it aims to identify and document the diversity of ritual plants and traditional medicine of the Balesari village community and analyze quantitative ethnobotanical indexes based on local knowledge, which contributes to the preservation of local knowledge, community adaptation to the environment, and strengthening biocultural resilience as a basis for sustainable conservation and development of traditional medicine. The research method used is a mixed method with an exploratory sequential design. Qualitative data were collected through interviews with the palace caretaker as a key informant and the palace area manager as an additional informant. Quantitative data were obtained through questionnaires to 92 Balesari village residents. Informants were selected through purposive sampling techniques followed by snowball sampling and qualitative and quantitative descriptive analyses were conducted using the ICF, RFC, and SUV indices. The results of the study identified 20 plant species from 12 families with a dominant Zingiberaceae that are used to treat diseases such as coughs, fever, worms, and to tighten the feminine area. The most frequently used plant parts are leaves with a PPUV value of 46.5% and rhizomes at 34.7%. Utilization of plant parts is carried out through boiling, grinding, or a combination of both. The ethnobotanical index shows a high consensus (ICF 0.75-1.00), the highest frequency of mention for Zingiber officinale and Kaempferia galanga (RFC=1), and the highest use value for Zingiber officinale (SUV=1.74) and the Moringaceae family (FUV=1.43). This reflects the strong local knowledge of the Balesari Village community in utilizing a diversity of ritual and health plants. This practice demonstrates the community's adaptation to environmental conditions in strengthening biocultural resilience through the transmission of traditional knowledge from generation to generation.